Aetiology of haemorrhagic cystitis: BK Polyomavirus and Adenovirus detection - Yoliswa Z. Chili; Menzi B. Nkosi; Nicky-Louise Byrne; Moepeng J. Maseko; Stephen N.J. Korsman; Gert U. Van Zyl (Southern African Journal of Infectious Diseases)
This case report details haemorrhagic cystitis in a 49-year-old female with chronic lymphocytic leukaemia (CLL), recurrent haematuria and detected BK polyomavirus (BKPyV) and adenovirus (HAdV) in urine. During chemotherapy cycles, quantitative polymerase chain reaction (PCR) assays found high HAdV load, similar to a HAdV-B2 genotype 78, a rare genotype that is closely related to HAdV-11.